2009
DOI: 10.3174/ajnr.a1564
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic Involvement and Its Impact on Clinical Disability in Patients with Multiple Sclerosis: A Diffusion Tensor Imaging Study at 3T

Abstract: BACKGROUND AND PURPOSE:Several studies suggest that grey matter involvement may play a role in multiple sclerosis (MS) pathology. Diffusion tensor imaging (DTI) at 3T was used to investigate the presence of damage to the normal-appearing thalamus in MS and its relationship with disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
67
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 50 publications
19
67
4
1
Order By: Relevance
“…Similar to our findings, an increased thalamic MD in patients with MS with different clinical disease phenotypes in comparison with healthy controls was found in these studies, on average. 9,16,17,31 However, contrary to our results, an increased thalamic FA has been described. 17,31 Several factors might contribute to explaining the discrepancy between ours and previous findings concerning baseline thalamic FA abnormalities, including the fact that previous studies recruited patients with different MS phenotypes, predominantly relapsing-onset MS, whereas we enrolled patients with PPMS only.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Similar to our findings, an increased thalamic MD in patients with MS with different clinical disease phenotypes in comparison with healthy controls was found in these studies, on average. 9,16,17,31 However, contrary to our results, an increased thalamic FA has been described. 17,31 Several factors might contribute to explaining the discrepancy between ours and previous findings concerning baseline thalamic FA abnormalities, including the fact that previous studies recruited patients with different MS phenotypes, predominantly relapsing-onset MS, whereas we enrolled patients with PPMS only.…”
Section: Discussioncontrasting
confidence: 56%
“…9,16,17,31 However, contrary to our results, an increased thalamic FA has been described. 17,31 Several factors might contribute to explaining the discrepancy between ours and previous findings concerning baseline thalamic FA abnormalities, including the fact that previous studies recruited patients with different MS phenotypes, predominantly relapsing-onset MS, whereas we enrolled patients with PPMS only. In addition, compared with the authors of previous studies, we applied a different strategy to sample the thalamus because we included the entire thalamus and used a GM thalamic mask, whereas other authors used relatively small regions of interest to select a small portion of the thalamus.…”
Section: Discussioncontrasting
confidence: 56%
“…[5][6][7] In particular, thalamic involvement is becoming increasingly recognized as a significant step in the development of clinical disability and memory impairment in multiple sclerosis. 8 Tovar-Moll et al 9 in an article published in the current issue of the American Journal of Neuroradiology demonstrate thalamic abnormalities in diffusion tensor metrics that correlate with clinical disability scores, in keeping with similar studies published on the subject. 10,11 Most interesting, Tovar-Moll et al reported increased fractional anisotropy (FA) and mean diffusivity (MD) values in the thalamus in comparison with matched controls.…”
Section: 2supporting
confidence: 50%
“…Overall, the article by Tovar-Moll et al 9 highlights the potential of diffusion tensor imaging techniques in the evaluation of gray matter pathology, particularly of the thalamus, and contributes to our understanding of the pathophysiology of multiple sclerosis.…”
Section: 2mentioning
confidence: 99%
“…15,16 DTI measures are able to identify alterations outside the focal lesions in the so-called normal-appearing white matter and normal-appearing gray matter that remain largely undetected with conventional MR imaging in patients with MS. 17 There is a growing interest in studying the DTI alterations of the SDGM in the different stages of the MS disease process. Previous studies suggested that SDGM DTI abnormalities are also present in patients with clinically isolated syndrome 18,19 and are associated with disability progression as well as cognitive dysfunctions in patients with MS. [20][21][22][23] Although different studies have investigated the associations between white matter lesions, brain atrophy, and DTI alteration in patients with MS, [24][25][26] the same relationships were not extensively investigated in healthy people whose pathophysiologic alteration of the brain cannot be attributable to the inflammatory process in the central nervous system. Therefore, in the current study, we aimed to investigate volumetric and DTI global, tissuespecific, and regional brain differences in a large cohort of healthy control (HC) patients, patients with relapsing-remitting MS (RRMS), and patients with progressive MS (PMS).…”
mentioning
confidence: 99%